Evaluating OPEN-MURDER Scenario Impact on Vocational Education: Mengevaluasi Dampak Skenario OPEN-MURDER pada Pendidikan Kejuruan - Permadani, Nahdia Putri; Sri Untari, Rahmania (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of the OPEN-MURDER scenario on the learning outcomes of 36 Software Engineering program students in Vocational Schools (SMK). Utilizing a quasi-experimental design, pretest-posttest assessments were conducted to measure learning outcomes before and after implementing OPEN-MURDER, focusing on mood, understanding, recall, digest, expand, and review. Results show a significant improvement, with pretest scores averaging 71.72 and posttest scores 89.53 (p < 0.05). The findings underscore OPEN-MURDER's positive influence on SMK students' learning outcomes, suggesting its potential as an effective teaching model to enhance motivation, problem-solving skills, and classroom engagement. Future research could explore comparative analyses with control groups and encourage educators to adopt OPEN-MURDER for innovative teaching practices. Highlight: OPEN-MURDER Evaluation: Assesses impact on vocational students' learning outcomes. Experimental Design: Utilizes pretest-posttest method to measure effectiveness. Positive Influence: Shows significant improvement in student learning outcomes post-implementation. Keywoard: Open-Murder Scenario, Learning Outcomes, Vocational Schools, Quasi-Experimental Design, Teaching Model.